The Eucommia ulmoides - Achyranthes bidentata pair and their active monomers exert synergistic therapeutic potential for osteoarthritis through the PI3K-AKT pathway - Chen, Chun; Lv, Lei; Huang, Yueying; Xie, Fangyuan; Gao, Mingzhu; Zeng, Sailiang; Wang, Zijun; Jiang, Xue; Zhan, Yangyang; Bao, Leilei (Frontiers in Pharmacology, 2025)
BackgroundOsteoarthritis is characterized by articular cartilage degradation, involving inflammation-mediated chondrocyte apoptosis and extracellular matrix destruction. Eucommia ulmoides and Achyranthes bidentata constitute a classic herbal pair for OA treatment, yet their combinatorial effects and molecular mechanisms remain unelucidated.MethodsThe EU-AB extract was prepared via aqueous decoction. An LPS-induced ATDC5 chondrocyte inflammatory model and an MIA-induced rat OA model were established. Therapeutic efficacy was evaluated using Lequesne scores, ELISA, Western blotting, and immunohistochemistry. Bioactive components were identified by HPLC-TOF/MS, while RNA-seq and molecular interaction analyses validated underlying mechanisms.ResultsThe EU-AB extract significantly suppressed the expression of matrix metalloproteinases (MMP-3/13) and inflammatory cytokines (NO, TNF-α, IL-6, IL-1β) in both ATDC5 cells and rat serum (P < 0.05). Concurrently, it reduced Lequesne scores and joint swelling in MIA-induced OA rats (P < 0.05) while ameliorating histopathological cartilage damage. Among 35 compounds identified by HPLC-TOF/MS, pinoresinol diglucoside (PIN) from EU and chikusetsusaponin Ⅳa (CHI) from AB demonstrated synergistic effects, downregulating pro-apoptotic proteins (Caspase-3/9, Bax) through activation of the PI3K-Akt pathway and promotion of Akt phosphorylation.ConclusionThe herbal pair aqueous extract suppresses osteoarthritis via the bioactive component group CHI-PIN, demonstrating synergistic anti-inflammatory effects in MIA rats, likely mediated by PI3K-Akt-regulated apoptosis.